All‐Vacuum‐Deposited Stoichiometrically Balanced Inorganic Cesium Lead Halide Perovskite Solar Cells with Stabilized Efficiency Exceeding 11%. Issue 11 (20th January 2017) - Chen, Chien‐Yu; Lin, Hung‐Yu; Chiang, Kai‐Ming; Tsai, Wei‐Lun; Huang, Yu‐Ching; Tsao, Cheng‐Si; Lin, Hao‐Wu
Abstract : Vacuum‐sublimed inorganic cesium lead halide perovskite thin films are prepared and integrated in all‐vacuum‐deposited solar cells. Special care is taken to determine the stoichiometric balance of the sublimation precursors, which has great influence on the device performance. The mixed halide devices exhibit exceptional stabilized power conversion efficiency (11.8%) and promising thermal and long‐term stabilities.